Developing a Functional Food Systems Literacy for Interdisciplinary Dynamic Learning Networks - Pope, Harley; de Frece, Annabel; Wells, Rebecca; Borrelli, Rosina; Ajates, Raquel; Arnall, Alex; Blake, Lauren J.; Dadios, Nikolaos; Hasnain, Saher; Ingram, John; Reed, Kelly; Sykes, Roger; et al. (Frontiers in Sustainable Food Systems, 2021)
The impact of human activity on the planet cannot be overstated. Food systems are at the centre of a tangled web of interactions affecting all life. They are a complex nexus that directly and indirectly affects, and is affected by, a diverse set of social, environmental and technological phenomena. The complexity and often intractability of these interactions have created a variety of food-related problems that people seek to address in a collaborative and interdisciplinary manner through the adoption of a holistic food systems perspective. However, operationalising a systemic approach to address food system challenges is not a guarantee of success or positive outcomes. This is largely due to the partiality inherent in taking a systems perspective, and the difficulty in communicating these different perspectives among stakeholders. A functional food systems literacy is therefore required to aid people in communicating and collaborating on food system problems within dynamic learning networks. The Interdisciplinary Food Systems Teaching and Learning (IFSTAL) programme has been operating since 2015 as a social learning system to develop a food systems pedagogy with a range of multi-sectoral partners. The findings in this paper arise out of iterative reflexive practice into our teaching approach and delivery methods by former and current staff. In order to foster integrative engagement on food system challenges, we propose and define a functional food systems literacy—a theoretical minimum that can aid diverse stakeholders to explore and intervene in food systems through more effective communication and collaboration. Derived from a reflective analysis of instruments and methods in delivering the IFSTAL programme, we provide a framework that disaggregates functional food systems literacy according to four knowledge types, and includes examples of skills and activities utilised in the IFSTAL programme to support learning in these different domains. We argue that claims to comprehensive food systems knowledge are unrealistic and therefore propose that a functional food systems literacy should focus on providing a means of navigating partial claims to knowledge and uncertainty as well as fostering effective collaboration. We believe that this will enhance the capabilities of stakeholders to work effectively within dynamic learning networks.